Assistance in Preparing Islamic Boarding School-Based Financial Reports Based on Psak No. 45 Parepare City Scope - Rismala, Rismala; Purnamasari, Rini (Abdi Masyarakat, 2024)
Islamic boarding schools have an important role in their development. not only in Parepare, but also throughout Indonesia and even in other Muslim countries. Islamic boarding schools are non-profit organizations because Islamic boarding schools are institutions that do not aim to make a profit for individuals or their managers. However, preparing Islamic boarding school financial reports is a form of managerial responsibility to interested parties, so the resulting reporting must be accountable and free from misstatement. The method used is a descriptive qualitative approach where we will hold meetings with Islamic boarding school foundation managers and will focus on financial reporting by providing assistance, discussions and questions and answers. The result of this service is that the financial reports of Islamic boarding schools in the Parepare City area have not fully adopted an accounting system that is in line with the Islamic Boarding School Accounting Guidelines. Currently, the reports submitted are limited to cash inflows and outflows, so Islamic Boarding School Accounting Guidelines are needed to provide non-binding, but supportive, direction in preparing financial reports.